1965
DOI: 10.1152/ajplegacy.1965.208.5.931
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular function in the newborn lamb

Abstract: The present study was initiated with the objective of evaluating in the newborn those aspects of ventricular mechanics which form the basis of the Frank-Starling relation, and which permit a determination of changes in the inotropic state of the heart. Left ventricular function was studied in lambs, 12 hr to 5 days old, utilizing a preparation designed to permit control and measurement of systemic arterial pressure (AP), cardiac output, heart rate (HR), and temperature. Continuous measurements of arterial Po2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

1970
1970
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 0 publications
3
27
0
Order By: Relevance
“…The combination of limited inotropic reserve coupled with a predominant systemic vasoconstrictive response to high infusion rates of dopamine as evidenced by increased aortic pressure and systemic vascular resistance, led to an inotropic:afterload mismatch resulting in the fall in cardiac output. It was interesting that Downing et al (21) using an in situ model of the newborn lamb heart, reported a decrease in stroke volume as systemic pressure (afterload) was increased within the range of aortic pressures that we observed in our study.…”
Section: Effects Of Dopumine Infusionsupporting
confidence: 55%
“…The combination of limited inotropic reserve coupled with a predominant systemic vasoconstrictive response to high infusion rates of dopamine as evidenced by increased aortic pressure and systemic vascular resistance, led to an inotropic:afterload mismatch resulting in the fall in cardiac output. It was interesting that Downing et al (21) using an in situ model of the newborn lamb heart, reported a decrease in stroke volume as systemic pressure (afterload) was increased within the range of aortic pressures that we observed in our study.…”
Section: Effects Of Dopumine Infusionsupporting
confidence: 55%
“…Likewise, measurements taken from isolated sheep myocardium performing isotonic (changing muscle length) contraction shows that both the extent and velocity of shortening are greater in the adult than the fetal heart over a range of applied loads (Friedman, 1972). From a whole-organ perspective, the increasing volume-density of myofibrils is consistent with the observation that stroke volume is significantly depressed in neonate lambs at afterloads that are modest for adults (Downing et al, 1965). From a whole-animal perspective, the hyperallometry of myofibril volume-density and absolute volume, and the associated increase in relative cardiac contractile performance, would augment cardiac output during in-pouch development and in the lead up to pouch vacation, and thus almost certainly facilitate the kangaroo's transition from ectothermy to endothermy (Hulbert, 1988;Loudon et al, 1985;Rose et al, 1998) and independent locomotion (Dawson, 2012).…”
Section: Discussionsupporting
confidence: 61%
“…As birth is associated with significant alterations of these determinants (36) and a doubling of cardiac output (26), there is significant interest and information available regarding the effects of isolated alterations of the determinants of cardiac output on cardiac function and output during the perinatal period. Most of the available information is focused on alterations of preload: studies on unanesthetized fetal and neonatal lambs have shown that an increase of preload is associated with an increase of stroke volume and cardiac output (10,15,22,24). The increase of pulmonary blood flow that occurs after the onset of respiration should increase left ventricular preload and this may account for some of the increase of cardiac output which occurs at birth.…”
Section: Discussionmentioning
confidence: 99%